The Evolving Landscape of Sustainability in the Hotel Industry: New Approaches and Their Success - Sikó, Botond (Acta Carolus Robertus, 2024)
Due to the growing importance of environmental protection, the countries of the world are striving to formulate regulations that protect the Planet, and these directly affect and apply to various businesses as well. In addition to these regulations, many large companies have recognized the importance of sustainability. On the one hand, large companies can achieve greater results with their efforts in a given time, and on the other hand, in parallel with the global spread of the idea, the purchase of sustainable products, the use of such services, and the preference of companies that take this into account are becoming more and more important for customers and buyers. Slowly but surely, sustainability is gaining strength in tourism and hospitality as well. In addition to environmental protection, waste management and reduction, energy saving and efficiency, and the reduction of harmful emissions are all increasingly important. All this, besides of protecting the environment, helps to reduce the energy costs and other expenses of companies after the implementation of the necessary investments. The aspirations appear, for example, in hotels ("green hotel"), restaurants and other areas of tourism. For companies, sustainable operation not only achieves the goals and results mentioned but also serves as a great marketing opportunity. Consciously planned and properly advertised, their activities can gain a competitive advantage and they can use their sustainability efforts as a strong attraction.The methodology includes two primary data collection methods, which are an interview with a hotel general manager and a questionnaire research done on the web with 129 participants.With the current research the author aims to provide information on Hungarian hotels’ sustainability efforts, their possibilities, achievements and further, still untapped potentials. The research includes an analysis of the institutional background, such as the Green Hotel award, the marketing value of such efforts, and the professional attitude towards the topic of sustainability from various actors of the hotel industry. Additional aim of the study is to provide insights into the attitudes of hotel guests towards sustainable tourism and identify the barriers and opportunities for the hotel industry to achieve sustainability. The findings of this research will inform hotel managers and stakeholders about the importance of sustainability in the industry and guide them in developing strategies to meet the growing demand for sustainable tourism.